Fighting the Machine: Co-constructing Team Based Evaluation for Non-Formal Learning. - Andrew Clapham; Raquel Barata (Museum & Society, 2024)
Museum educators increasingly face demands to evaluate the ‘value’ of non-formal learning (NF-L). This paper offers a unique international and multi-educator perspective on how informants from Portugal, Italy and the United Kingdom navigated these demands. Analysis of interview data highlighted that, although working in three different countries, most of these educators had experienced evaluation as accountability (and disciplinary) focused; employing methodologies inappropriate for evaluating NF-L and rarely team based. Drawing on a composite theoretical framework, these data led to co-constructing the Team Based Evaluation (TBE) model. Two case studies map how TBE was enacted and recommendations concerning organizational change are made. The paper concludes that, whilst set within the museum education space, TBE can be applied across evaluation contexts and micro and macro scales. Locally, TBE can mediate rich evidence and develop team working practices. Nationally and internationally, it can contribute to resetting evaluation from an accountability and disciplinary ‘machine’ to a dialogic, democratic and developmental activity.